2017
DOI: 10.1155/2017/2628968
|View full text |Cite
|
Sign up to set email alerts
|

Association of Irisin Plasma Levels with Anthropometric Parameters in Children with Underweight, Normal Weight, Overweight, and Obesity

Abstract: The correlations between irisin levels, physical activity, and anthropometric measurements have been extensively described in adults with considerable controversy, but little evidence about these relationships has been found in children. The objective of this study is to correlate the plasma levels of irisin in underweight, normal weight, overweight, and obese children with anthropometric parameters and physical activity levels. A cross-sample of 40 children was divided into the following groups on the basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 48 publications
3
28
1
Order By: Relevance
“…As such, there is currently no universally accepted ‘reference range’ or normal value for circulating irisin in healthy individuals and some even question its existence [ 39 ]. Although it has been suggested that a ‘normal’ circulating concentration of irisin may fall in the narrow range of 3.6–4.6 ng/ml [ 40 ], plasma irisin levels similar to those observed in the present study have been independently reported previously [ 41 , 42 ]. Moreover, the ELISA used in the present study has been previously tested against both Western blotting [ 43 ] and mass spectrometry [ 44 ].…”
Section: Discussionsupporting
confidence: 86%
“…As such, there is currently no universally accepted ‘reference range’ or normal value for circulating irisin in healthy individuals and some even question its existence [ 39 ]. Although it has been suggested that a ‘normal’ circulating concentration of irisin may fall in the narrow range of 3.6–4.6 ng/ml [ 40 ], plasma irisin levels similar to those observed in the present study have been independently reported previously [ 41 , 42 ]. Moreover, the ELISA used in the present study has been previously tested against both Western blotting [ 43 ] and mass spectrometry [ 44 ].…”
Section: Discussionsupporting
confidence: 86%
“…These concentrations were higher (P > 0.05) than those observed in the group with normal BMI. This is consistent with the results of another study in which the overweight and obese groups showed no difference compared with the normal weight group (29).…”
Section: Discussionsupporting
confidence: 92%
“…Previous work from Huh and coworkers showed that circulating irisin declines in parallel with age-related muscle loss, and documented a strong positive association between irisin and biceps circumference, implying that muscle mass is the main determinant of circulating irisin levels in humans 13 . Other www.nature.com/scientificreports www.nature.com/scientificreports/ studies prompted similar evidence of a positive correlation between irisin and fat-free mass 15,18,40,41 . Hence, the positive correlation observed between irisin and muscle mass agrees with the divergent obese phenotypes of the populations studied 42 .…”
Section: Discussionmentioning
confidence: 75%
“…Although dual X-ray absorptiometry (DXA) is considered the gold standard for the assessment of body composition, the very obese phenotype of the patients herein studied exceeded the DXA weigh limit in many cases. Nevertheless, BIA has already proven useful in clinical settings investigating irisin in relation to body composition 15,40,41,46 . Because our study was conducted in PWS patients with severe obesity, its results may not extend to non-obese PWS patients.…”
Section: Discussionmentioning
confidence: 99%